The Pricing Process in Consumer Credit: Discussion - Smith, Tynan (Journal of Finance, 1964)
Tynan Smith, The Pricing Process in Consumer Credit: Discussion, The Journal of Finance, Vol. 19, No. 2, Part 1: Papers and Proceedings of the Twenty-Second Annual Meeting of the American Finance Association, Boston, Massachusetts, December 27-29, 1963 (May, 1964), pp. 234-236